Caracterização limnológica e inventário de diversidade das comunidades de macrófitas em cinco lagos tropicais: composição florística, biomassa e macroinvertebrados associados - Tavares, Katia Sendra (Universidade Federal de São Carlos, 2007)
In the present study five tropical lakes located in Minas Gerais State were studied. The methodology followed the scheme of rapid inventories of aquatic diversity as used in the AquaRAP Program. Four lakes belonging to the Lacustrine System of the Middle Rio Doce Valley (Carioca, Verde, Águas Claras e Almécega) were sampled in the rainy (December 2003) and dry (May 2004). Tropeiros Lake located in the wetlands of Piumhi River backwaters, a River formerly belonging to Rio Grande basin, but that had its course changed to São Francisco basin, was sampled in October 2006, at the beginning of the rainy season. The lakes of the Middle Rio Doce Valley had high water transparency (Secchi Disk readings varying from 2.0 to 2.9m), low water conductivity (20 to 38 µScm-1), pH slightly acid to slightly alkaline (6.2 8,4) and well oxygenated (3.9 to 7.8 mg/L). All lakes were mesotrophic in December, 2003 (Total P varying from 17.38 to 21.62µg/L), but oligotrophic in May, 2004, except Lake Carioca which was mesotrophic. Tropeiros Lake was found to be mesotrophic at the sampling time. Total P varying from 23.2 a 45.4 µg/L) pH varying from neutral to alkaline (7.0 to 9.2), moderate water conductivity (39.6 to 54.7 µScm-1) and oxygen concentrations varying from low to moderate (1.5 a 6.1mg/L). The occurrence of a El-Niño event in the years of 2002 and 2003 altered the regional pluviometric regime in the region of the Valley of the Middle Rio Doce, MG, causing almost 40% reduction of the total annual precipitation, with a marked decrease of the lakes water level. As a consequence, macrophyte communities richness was low, with a total of 20 species of macrophytes only. On the other hand a high species richness was observed in Tropeiros Lake, with a total of 28 species registered. Among the studied lakes in the Middle Rio Doce Valley no relationship was found between the biomass of macrophytes per unity area and the size of the lakes nor between the amount of biomass and the trophic state of the lakes. In all five lakes studied the macroinvertebrates communities associated with macrophytes were mainly constituted by Chironomidae (Diptera) a pattern found in freshwaters world wide. A linear positive relationship was found between the macrophyte biomass and the associated macroinvertebrates biomass in Tropeiros Lake. Tropeiros Lake, although inventoried once had a higher macrophyte taxa richness, higher macrophyte biomass and higher associated macroinvertebrates biomass, probably representing a hot-spot of diversity for both, macrophytes and associated macroinvertebrates communities.
Keywords: Limnologia; Diversidade biológica; Plantas aquáticas; Mudanças climáticas; Fauna associada; CIENCIAS BIOLOGICAS::ECOLOGIA